Study on Coarse Recycled Concrete Aggregate - Singh, Rahul; Nayak, Dheeresh Kumar; Kumar, Rajesh; Kumar, Veerendra (Horizon Research Publishing, 2022)
The use of recycled concrete aggregate (RCA) is one of the best solutions to mitigate the problem of ecological instability created by concrete waste. RCA has less crushing strength, impact resistance, specific gravity, and more water absorption capacity than the natural aggregate (NA). To overcome the compromised properties of RCA, a comprehensive study supported by the experimental investigation is required. This paper prescribes a methodology based on experimental investigation for the use of coarse-RCA (C-RCA) of size (4.75-20mm) as 100% replacement of coarse-NA in fresh concrete. A “remodified two-stage mixing approach (R-TSMA)” supported by a physical treatment method is proposed here to increase the bond strength between RCA and new mortar. Micro-structure of RCA-C has been studied via optical microscope as well as Scanning Electron Microscope (SEM). Effect of parent concrete quality is influential only at early curing age (7 and 14 days), but after 28 days of curing its influence reduced, such that RCA-C sample showed 5% higher compressive strength and about 4% higher in flexural strength than NA-C. At 90 days of curing, all RCA samples showed higher compressive and flexural strength than NA-C. Similarly, carbonation curing enhanced the strength of RCA-C by higher margin than NA-C.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Compressive Strength; Flexural Strength; ITZ; Recycled Concrete Aggregate; Splitting Tensile Strength